Analysis of the Relationship Between Open Defecation Free Behavior and Water Quality in the Kalitebu River, Kali Kedinding Subdistrict, Surabaya - Nampira, Anisa Apriliani; Afrianisa, Rodu Dhuha; Pramestyawati, Talent Nia (Lembaga Penelitian dan Pengabdian kepada Masyarakat ITATS, 2025)
The Kali Tebu River in Tanah Kali Kedinding Village, Kenjeran District, Surabaya City, is often used by many people to defecate. Data collected by the Tanah Kali Kedinding Community Health Center in 2023 shows that 48 heads of families (KK), or 0.30% of the total population, are still involved in Open Defecation (Open Defecation) in waterways that flow directly into the river. into the Kali Tebu River, this can pollute river water, changing the quality of river water. The aim of the research is to analyze the results of river water quality tests, water quality status. In this research, a questionnaire was filled out to find out the community profile, then tested the parameters based on Minister of Environment and Forestry Regulation No. 68 of 2016 which consists of TSS, pH, BOD, COD, Fatty Oil, Ammonia, and Total Coliform. Then compare the quality status of the Storet method and the Pollution Index (IP) which is guided by Minister of Environment Decree No. 115 of 2003 with River Water Quality in accordance with PP RI No. 22 of 2021 . The test results for the TSS, BOD, COD, Ammonia, Fatty Oil and Total Coliform parameters of the Kali Tebu river do not meet the class quality standards in accordance with Government Regulation no. 22 of 2021, while the pH, COD and fatty oil parameters are compliant. Then the water quality status in the Kali Tebu River was determined using the storet method at points 1 – 3, all of which were included in the heavily polluted category with result values of -102, -100, -98. Meanwhile, to determine water quality status using the average Pollution Index at points 1 - 3, it is included in the heavily polluted category with PIj values 10, namely 20, 22, 23.